CD4+ T-Cell Endogenous Cystathionine γ Lyase–Hydrogen Sulfide Attenuates Hypertension by Sulfhydrating Liver Kinase B1 to Promote T Regulatory Cell Differentiation and Proliferation. Issue 18 (3rd November 2020) - Cui, Changting; Fan, Jinghui; Zeng, Qiang; Cai, Junyan; Chen, Yongzeng; Chen, Zhenzhen; Wang, Wenjie; Li, Shuang yue; Cui, Qinghua; Yang, Jichun; Tang, Chaoshu; Xu, Guoheng; et al.
Abstract : Background: Hydrogen sulfide (H2 S) has antihypertension and anti-inflammatory effects, and its endogenous-generation key enzyme cystathionine γ lyase (CSE) is expressed in CD4 + T cells. However, the role of CD4 + T-cell endogenous CSE/H2 S in the development of hypertension is unclear. Methods: Peripheral blood lymphocytes were isolated from hypertensive patients or spontaneously hypertensive rats, then H2 S production and expression of its generation enzymes, cystathionine β synthase and CSE, were measured to determine the major H2 S generation system changes in hypertension. Mice with CSE-specific knockout in T cells (conditional knockout, by CD4 cre mice hybridization) and CD4 null mice were generated for investigating the pathophysiological relevance of the CSE/H2 S system. Results: In lymphocytes, H2 S from CSE, but not cystathionine β synthase, responded to blood pressure changes, supported by lymphocyte CSE protein changes and a negative correlation between H2 S production with systolic blood pressure and diastolic blood pressure, but positive correlation with the serum level of interleukin 10 (an anti-inflammatory cytokine). Deletion of CSE in T cells elevated BP (5–8 mm Hg) under the physiological condition and exacerbated angiotensin II–induced hypertension. In keeping with hypertension, mesenteric artery dilation impaired association with arterial inflammation, an effect attributed to reduced immunoinhibitory T regulatory cell (Treg) numbers in the blood and kidney, thus causing excess CD4 + and CD8 + T cell infiltration in perivascular adipose tissues and kidney. CSE knockout CD4 + T cell transfer into CD4 null mice, also showed the similar phenotypes' confirming the role of endogenous CSE/H2 S action. Adoptive transfer of Tregs (to conditional knockout mice) reversed hypertension, vascular relaxation impairment, and immunocyte infiltration, which confirmed that conditional knockout–induced hypertension was attributable, in part, to the reduced Treg numbers. Mechanistically, endogenous CSE/H2 S promoted Treg differentiation and proliferation by activating AMP-activated protein kinase. In part, it depended on activation of its upstream kinase, liver kinase B1, by sulfhydration to facilitate its substrate binding and phosphorylation. Conclusion: The constitutive sulfhydration of liver kinase B1 by CSE-derived H2 S activates its target kinase, AMP-activated protein kinase, and promotes Treg differentiation and proliferation, which attenuates the vascular and renal immune-inflammation, thereby preventing hypertension. Abstract : Supplemental Digital Content is available in the text.